Storeroom at Bridesburg plant - Rohm and Haas Company (Exterior views of Charles Lennig and Company plant in Bridesburg, 1931)
Exterior view of the storeroom (Building 18) at the Charles Lennig and Company chemical manufacturing plant in Bridesburg, a neighborhood located along the Delaware River in the Northeast section of Philadelphia, Pennsylvania. Charles Lennig and Company operated as a subsidiary of the Rohm and Haas Company, an international chemical company headquartered in Philadelphia, from 1920 to 1947.
Keywords: Chemical industry; Charles Lennig and Company, Inc.; Pennsylvania--Philadelphia--Bridesburg; Rohm and Haas Company; Corporations